Indole-3-Carbinol Selectively Prevents Chronic Stress-Induced Depression-but not Anxiety-Like Behaviors via Suppressing Pro-Inflammatory Cytokine Production and Oxido-Nitrosative Stress in the Brain - Pan, Shengying; Ma, Yaoying; Yang, Rongrong; Lu, Xu; You, Qingsheng; Ye, Ting; Huang, Chao (Frontiers in Pharmacology, 2022)
Indole-3-carbinol (I3C), a phytochemical enriched in most cruciferous vegetables, has been shown to display various biological activities such as anti-oxidative stress, anti-inflammation, and anti-carcinogenesis. In this study, we investigated the regulatory effect of I3C on chronic stress-induced behavioral abnormalities in mice. Results showed that repeated I3C treatment at the dose of 10, 30, and 60 mg/kg prevented chronic social defeat stress (CSDS)-induced behavioral abnormalities in the tail suspension test, forced swimming test, sucrose preference test, and social interaction test in mice, and did not affect CSDS-induced behavioral abnormalities in the elevated plus maze, light-dark test, and open-field test, suggesting that the I3C treatment selectively prevents the onset of depression- but not anxiety-like behaviors in chronically stressed mice. Further analysis demonstrated that repeated I3C treatment (60 mg/kg, 10 days) prevented CSDS-induced increases in levels of interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α) mRNA and protein, but did not affect CSDS-induced decreases in levels of IL-4, IL-10, and Ym-1 mRNA and/or protein in the hippocampus and prefrontal cortex, suggesting that I3C can selectively prevent chronic stress-induced pro-inflammatory but not anti-inflammatory responses in the brain. Further analysis showed that repeated I3C treatment (60 mg/kg, 10 days) prevented CSDS-induced increases in levels of nitrite and malondialdehyde (MDA), decreases in contents of glutathione (GSH), and decreases in levels of brain derived neurotrophic factor (BDNF) protein in the hippocampus and prefrontal cortex. These results demonstrated that I3C selectively prevents chronic stress-induced depression-like behaviors in mice likely through suppressing neuroinflammation and oxido-nitrosative stress in the brain.